Evaluation of Seed Longevity of Diploknema butyracea - Bahar, Nawa; Singh, V. R. R.; Sharma, Preeti (Indian Forester, 2011)
Diploknema butyracea is a fast growing multipurpose tree species belonging to family Sapotaceae. Seeds of D. butyracea were stored for different storage period at ambient condition and various seed and seedling parameters were studied. The investigation revealed that seeds of this species are short - lived. Keeping in view the most desirable characters viz., germination per cent, germination value, seed weight, seed value and seed vigour of fresh seed lot were determined among all other storage periods at ambient condition.